Nomenclatural notes on Kalanchoe globulifera (Crassulaceae subfam. Kalanchooideae), the species under which the economically important K. blossfeldiana was at first recognised, at the rank of variety, as K. globulifera var. coccinea - Smith, Gideon F. (Phytotaxa, 2023)
The nomenclature associated with the name Kalanchoe globulifera (Crassulaceae subfam. Kalanchooideae) is reviewed. The economically important K. blossfeldiana was first described at the rank of variety under K. globulifera, as K. globulifera var. coccinea. This taxonomic view persisted for several decades after K. globulifera var. coccinea was elevated to species rank as K. blossfeldiana, because the combination K. coccinea was not available. The type of the name K. globulifera is clarified in a second-step lectotypification.